Peningkatan Hasil Belajar Pendidikan Agama Katolik dan Budi Pekerti Melalui Metode Problem Based Learning (PBL) pada Materi Sakramen Ekaristi di Kelas VIII SMP Marsudirini Tualang - Dina Ria Pinem; Yusmanto Yusmanto; Busri Busri (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This study aims to determine the improvement of learning outcomes of Catholic Religious Education and Character Education for class VIII (eight) students at SMP Marsudirini Tualang through the problem based learning (PBL) method. This type of research is classroom action research (PTK). The research sample consisted of 26 students. The research was conducted in 2 (two) cycles, each cycle consisting of 4 (four) components, namely planning, action, observation and reflection. Based on data analysis, the increase in student learning outcomes in cycle I was 75% while in cycle II it increased by 91%. Therefore, based on the results of the study, it can be concluded that the problem based learning (PBL) learning method can improve student learning outcomes in the subject of Catholic Religious Education and Character Education for class VIII (eight) at SMP Marsudirini Tualang.